Evaluating The Fraud Triangle Perspective in India’s Pharmaceutical Sector - Dabar, Himanshoo; Guniganti, Sunitha (International Journal of Accounting and Economics Studies, 2025)
The research paper examines the usefulness of the Fraud Triangle Theory (FTT) in describing ‎financial statement fraud in the context of the Indian pharmaceutical industry, where empirical ‎research at a large scale is scarce. The analysis is done using a panel dataset of 135 listed ‎pharmaceutical firms on NSE and BSE in the period 2014-2022, where the indicators of pressure, ‎opportunity, and rationalization are taken (liquidity, solvency, asset turnover, firm size, and ‎profitability ratios) to predict the occurrence of fraudulent financial reporting with the fraud proxy ‎‎(qualified opinion, emphasis of matter content). The findings demonstrate that solvency risk (debt-to-equity ratio) is a huge determinant and more likely to generate fraud, and asset-based firms are ‎less likely to declare fraudulent statements. Other pressure, opportunity, and rationalization proxies ‎have weak explanatory power, implying that FTT has a minor role in explaining the levels of fraud ‎in this industry. The results are informative to the auditors, regulators, and managers as they ‎draw attention to the red flags associated with leverage, and the necessity to monitor financially ‎strained pharmaceutical companies more closely, as well as to the shortcomings of using FTT and ‎audit-opinion-based proxies in high-R&D industries. It is one of the first large-scale empirical ‎estimates of the Fraud Triangle Theory in the pharmaceutical industry in India that provides ‎industry-specific results and helps to fill the gaps in the research on fraud detection and regulation ‎in the emerging economy‎.
Keywords: Financial Statement Fraud; Pharmaceutical Companies; Fraud Triangle Theory; Audit Opinion; India